Business Process Reengineering pada Sistem Perekrutan Tenaga Kerja Outsourcing di PT Dapensi Trio Usaha - Alia Putri sari; Putri Maharani Nur Alifa; Marisa Lina manullang; Sri Andayani (Journal Of Informatics And Busisnes, 2026)
PT Depensi Trio Usaha is a private company engaged in outsourcing, an affiliate of PT Pos Indonesia (Persero). Its recruitment process still faces several obstacles, such as manual processes, limited applicant databases, and inefficient selection and management of the required workforce. This study aims to analyze and redesign the recruitment process using the Business Process Reengineering (BPR) method. The redesign process involves three main stages: rethink, redesign, and retool, with the initial identification of Critical Success Factors (CSFs) and Key Performance Indicators (KPIs). The desired solution is a shift to fully digitizing the recruitment process through online forms and the use of databases. The results of this study indicate that the implementation of BPR can improve the efficiency and effectiveness of the recruitment process by digitizing registration, selection, and workforce data management.